Choosing Not to Give Birth at a Health Facility in Nigeria: Where and Why?. Issue 2 (3rd April 2018) - Yaya, Sanni; Amouzou, Agbessi; Ekholuenetale, Michael; Udenigwe, Ogochukwu; Hudani, Alzahra; Shah, Vaibhav; Bishwajit, Ghose
Abstract: The objective of this study was to examine regional variations in the self-reported causes of choosing not to give birth at a health facility in Nigeria. Cross-sectional data on 24, 033 community dwelling women aged 15–49 years were collected from the Nigeria Demographic and Health Surveys (NDHS) conducted in 2008 and 2013. In both surveys a large proportion of the women mentioned facility childbirth as not necessary: 55.6% (53.3–57.8) in 2008 and 35.6% (34.0–37.2) in 2013. Poor transportation, not being customary, and costliness were each reported by around 10% of the respondents. The regression analysis showed significant regional variations in the prevalence of the self-reported causes of non-utilization. Women in the northern regions of the country were more likely to regard facility childbirth as unnecessary and to complain about transportation and financial difficulties.